Solve -n - 2*j - 15 = 0, 9*j - 6*j = -3*n - 30 for n.
-5
Solve -3*t + 12 = -5*w, 3*t + 2*w - 9 = 3 for t.
4
Solve -24*j - 4*q = -25*j - 7, 9*q = j + 22 for j.
5
Solve 0 = p + 2*f + 5, 9 = -5*p + 8*f - 10*f for p.
-1
Solve -8 = c - 5*r, -6*r + 2*r = 5*c - 18 for c.
2
Solve 3*d = 4*p - 3, -81*p + 86*p - 5*d = 10 for p.
-3
Solve 0 = -4*m - 10*v + 14*v - 4, -4*m = -v - 2 for m.
1
Solve 0 = -3*p + 4*k - 2, -p + 28*k = 27*k for p.
2
Solve -3*y = -5*h - 3, -3*h + 3*y - 3 = -0 for h.
0
Solve 2*m - 10 = 2*g, -m = -5*g + 3 - 24 for g.
-4